Anisotropic composite scaffolds containing strontium-substituted hydroxyapatite nanofibers and collagen as bone substitutes - Fu-Yin Hsu; Tzu-Fang Hsu; Whei-Lin Pan; Shiao-Wen Tsai (Polymer Testing)
Various bone grafting materials have been developed to address bone defects caused by tumor resection and skeletal abnormalities. In this study, an anisotropic composite scaffold incorporating strontium-substituted hydroxyapatite (SrHA) nanofibers and collagen was designed to replicate the anisotropic structure of native bone tissue. The physical, chemical, and biological properties of these composite scaffolds were thoroughly evaluated. First, the aligned SrHA nanofibrous membrane was fabricated using an electrospinning method. Next, multiple SrHA nanofibrous membranes were stacked layer by layer to create a SrHA nanofibrous matrix. A collagen solution was subsequently added to the SrHA nanofibrous matrix, followed by lyophilization to form the composite scaffold. Finally, the composite scaffold was crosslinked using EDC. SEM confirmed the successful fabrication of the composite scaffold, which consisted of aligned SrHA nanofibrous membranes and collagen. Compression testing revealed the Young's modulus of the composite scaffold and demonstrated that the SrHA nanofibers reinforced the scaffold structure, compensating for the weaker mechanical properties of the scaffold itself while highlighting its anisotropic characteristics. The biological evaluation revealed that the proliferation, alkaline phosphatase (ALP) activity and BSP expression in MG63 osteoblast-like cells cultured on the composite scaffold were significantly greater than those of MG63 cells cultured on the collagen scaffold.